Förebygg och åtgärda mobbning på arbetsplatser - Zetterberg, Kerstin (SLU/Dept. of Landscape Architecture, Planning and Management (from 130101), 2004)
Bullying in workplaces has been a growing problem the last ten years. Anyone can be a victim or a bully. Either you are a leader or a worker a bullying situation can be activated. There is no difference between ages, line of business, education or the size of the firm. A person is defined as bullied if he or she is repeatedly subjected to negative acts in the workplace. However, to be a victim of such bullying one must also feel inferiority in defending oneself in the actual situation. Bullying often occurs when situations or conditions at the workplace are unsatisfactory. Employers are always responsible for the working environment at the workplace. Victims of bullying very often develop psychological stress. To prevent bullying you have to accept the fact that bullying exists. If the company has a clear policy against bullying and a plan for action if the problem occurs, it will be easier to handle the situation. It is important to have good relation between leaders and workers. The responsible person for the workplaces must have knowledge about leadership and psychology. If there is a content atmosphere among the workers at the workplace, there is no risk of bullying.